Tour-Pal: with you, anywhere - Tiwari, Aishwarya; Kesharwani, Alkesha; Ajani, Samir (International Journal of Computer Sciences and Engineering, 2025)
This project presents the architecture and implementation of a location based application, called Tour-Pal. It provides search service based on the user’s current location. If the user is in any emergency situation or needs to find places (such as hospital, medical shop, police station etc) this application will give the nearest available addresses of the place searched. All these elements will change accordingly as the position of the user changes. Users are permitted to get tour guidance information that they are in need of, anytime and anywhere. The tourist data can be browsed using an Internet map service, Google Maps. This application can be used by people new to the city too, for finding places like hospital, bus stop, railway station, airport, auto-stand, hotels etc also to find places that are either required in case of emergency or in day to day life. The idea behind the system is simple: using personal, mobile wireless computing devices, user can get the tourism guide ubiquitously.